Studi Semiotika Teks Diskursus “China Threat” di Kalangan Elit Indonesia - Zudan Rosyidi; Abu Fanani; Murni Fidiyanti; Jauharoti Alfin (Asosiasi Pendidikan Tinggi Ilmu Komuniasi (ASPIKOM) Wilayah Riau, 2024)
This research departs from the problem of discussions on Foreign Workers (TKA) and China's claims to parts of the North Natuna Sea (LNU) area. Actively several parties who are considered state actors, such as government officials and non-state actors such as politicians, academics, and also ordinary people shape this discourse. The research method used integrates text semiotic methods with post-structuralist securitization concepts. Semiotics is used to select and analyze signs in text and non-text form as well as post-structuralist securtization as a model in analyzing these signs.These actors produced a number of signs (signs) in the form of indices, icons and symbols which were narrated both orally and in writing to represent the discourse of the